Cognitive Procedural Learning in Amnesia - Schmidtke, Klaus; Handschu, René; Vollmer, Heike (Brain and cognition, 1996)
This group study examined the role of residual declarative memory and task-specific cognitive abilities for cognitive procedural learning in amnesia. 20 amnesic patients and 40 control subjects were studied, using four new cognitive tasks, as well as the Tower of Hanoi and a Mirror Reading task. On the cognitive tasks, but not on Mirror Reading, the learning of amnesic patients was significantly impaired relative to controls. Between- and within-group differences in learning were found to be statistically related to cognitive abilities that are involved in the processing of the procedural tasks. In amnesic patients, significant effects of residual declarative memory on learning scores were not observed, but there was indirect evidence for a role of memory in two tasks. The analysis of the correlative relationship between absolute procedural task performances and cognitive abilities indicated a prolonged dependence on nonspecific intellectual abilities in amnesic patients, suggesting a retarded transition to more advanced stages of skill acquisition.